2021
DOI: 10.1097/nna.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of a Collaborative Regional Evidence-Based Practice Fellowship

Abstract: sharing resources, increasing professional knowledge and skills, improving patient outcomes, and strengthening organizational cultures of quality and safety. This article describes the long-term outcomes of a regional collaborative evidence-based practice fellowship. Results reveal the fellowship had a measurable positive impact on fellows' evidence-based practice knowledge and practice, project outcomes, professional growth, and the culture of excellence within partner organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Academic-practice partnerships have been recognised as a potential means of overcoming many key barriers in EBNP. 8 9 The American Association of Colleges of Nursing (AACN) has recommended academic-practice partnerships as the key mechanism in advancing healthcare to strengthen the involvement of nurses in clinical practice and to prepare them to lead change. 10 The term academic-practice partnerships refers to a type of strategic relationship between educational and clinical practice settings, which can promote the mutual interests related to nursing practice, education and research by leveraging the talents and strengths of both sides.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Academic-practice partnerships have been recognised as a potential means of overcoming many key barriers in EBNP. 8 9 The American Association of Colleges of Nursing (AACN) has recommended academic-practice partnerships as the key mechanism in advancing healthcare to strengthen the involvement of nurses in clinical practice and to prepare them to lead change. 10 The term academic-practice partnerships refers to a type of strategic relationship between educational and clinical practice settings, which can promote the mutual interests related to nursing practice, education and research by leveraging the talents and strengths of both sides.…”
Section: Introductionmentioning
confidence: 99%
“… 12 15 16 Some literature also suggested that academic-practice partnerships had the potential to overcome some crucial barriers (eg, inadequate EBNP competence and training of clinical practice nurses, lack of patients and practice environments for academic nurses) to evidence-based practice by sharing resources and qualified personnel in clinical and academic settings. 8 9 17 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations